Performing Authorship: Self-inscription and Corporeality in the Cinema, by Cecilia Sayad - Laura Busetta (Alphaville: Journal of Film and Screen Media, 2014)
The issue of authorship has been widely discussed in Film Studies. Through phases of critical idealisation, abstraction and even rejection, the figure of the author has attracted sustained interest in film theory debates, giving rise to, for instance, the well-known reflections of the French politique des auteurs, or Andrew Sarris’s auteur theory; and it has survived until today, as evidenced by the recent publication of several contributions, including those by Paisley Livingston, Aaron Meskin, and Berys Gaut. If the “romantic model” looked at the author as the heart of the text, the poststructural revision has focused, to the contrary, on the author’s absence; the theory of the death of the author seemed to establish a “desubjectification”, which was deemed necessary to the analysis of every work of art, as in the contributions of Roland Barthes and Michel Foucault.